Outage Analysis of THz-Enabled IRS-Assisted Multi-User Space–Air—Ground Integrated Networks - Ahmed M. Benaya; Mohamed I. AlHajri; Mahmoud H. Ismail; Mohamed S. Hassan; Taha Landolsi (IEEE Open Journal of the Communications Society)
Ubiquitous connectivity through the integration of terrestrial and non-terrestrial networks has become one of the crucial usage scenarios in the sixth generation (6G) vision. In this paper, we analyze the outage performance of a multi-user aerial intelligent reflecting surface (IRS)-assisted space-air-ground integrated network (SAGIN) operating in the terahertz (THz) band. The system consists of a low earth orbit (LEO) satellite that communicates with a group of user equipment (UEs) through a terrestrial base station (TBS) relay. Due to the presence of obstacles and shadowing, a high-altitude platform station (HAPS)-mounted IRS is utilized to assist the communication scenario. We derive exact closed-form expressions for the outage probabilities at the UEs through the TBS relay and through the HAPS using the multivariate Fox’s H-function assuming optimal IRS phase shifts. Moreover, we derive approximate closed-form expressions using the central limit theory (CLT) for a sufficiently large number of IRS elements for both optimal phase shifts and phase shift estimation errors cases. Monte Carlo simulations are conducted to validate the derived expressions. Simulation results demonstrate that deploying HAPS-mounted IRS significantly enhances the outage performance at lower satellite transmit power and provides coverage over larger service areas.